Development of biochar-based controlled-release nano-fertilizers from date industry waste for enhanced nutrient and water management - Samira S. Elsabagh; Elsayed A. Elkhatib; Mohamed Rashad (Biomass and Bioenergy, 2026)

Potential use of nanoparticles produced from byproducts of drinking water industry in stabilizing arsenic in alkaline-contaminated soils - Mohamed L. Moharem; Hala M. Hamadeen; Mohamed O. Mesalem; Elsayed A. Elkhatib (Environmental Geochemistry and Health, 2023)
The stabilization of heavy metals in soils is considered a cost-effective and environmentally sustainable remediation approach. In the current study, the applicability of water treatment residual nanoparticles (nWTRs) with the particle size ranged from 45 to 96 nm was evaluated for its efficacy in reducing arsenic mobility in clayey and sandy contaminated alkaline soils. Sorption isotherms, kinetics, speciation and fractionation studies were performed. Sorption equilibrium and kinetics studies revealed that As sorption by nWTRs-amended soils followed Langmuir and second-order/power function models. The maximum As sorption capacity (q max ) of Langmuir increased up to 21- and 15-folds in clayey and sandy soils, respectively, as a result of nWTRs application at 0.3% rate. A drastic reduction in non-residual (NORS) As fraction from 80.2 and 51.49% to 11.25 and 14.42% for clayey and sandy soils, respectively, at 0.3% nWTRs application rate was observed, whereas residual (RS) As fraction in both studied soils strongly increased following nWTRs application. The decline in percentage of As mobile form (arsenious acid) in both soils after nWTRs application indicated the strong effect of nWTRs on As immobilization in contaminated soils. Furthermore, Fourier transmission infrared spectroscopy analysis suggested reaction mechanisms between As and the surfaces of amorphous Fe and Al oxides of nWTRs through OH groups. This study highlights the effective management approach of using nWTRs as soil amendment to stabilize As in contaminated alkaline soils.

Efficient removal of Cd (II) from contaminated water and soils using nanoparticles from nitrogen fertilizer industry waste - Elsayed Elkhatib; Ahmed Mahdy; Ayman Mahmoud; Mohamed Moharem (Journal of Environmental Health Science and Engineering, 2019)

Using nanoparticles from water treatment residuals to reduce the mobility and phytoavailability of Cd and Pb in biosolid-amended soils - Elsayed A. Elkhatib; Fatma Sherif; Mahrous Kandil; Ahmed Mahdy; Mohamed Moharem; Abdulla A. Al-Basri (Environmental Geochemistry and Health, 2018)

Immobilization of copper, lead, and nickel in two arid soils amended with biosolids: effect of drinking water treatment residuals - Elsayed A. Elkhatib; Mohamed L. Moharem (Journal of Soils and Sediments, 2015)

Green synthesis of nanoparticles by milling residues of water treatment - Elsayed A. Elkhatib; Ahmed M. Mahdy; Karam A. Salama (Environmental Chemistry Letters, 2015)

Effects of drinking water treatment residuals on nickel retention in soils: a macroscopic and thermodynamic study - Elsayed A. Elkhatib; Ahmed M. Mahdy; Mohamed M. ElManeah (Journal of Soils and Sediments, 2013)